Prebiotic potential of green banana flour: impact on gut microbiota modulation and microbial metabolic activity in a murine model - Baek, Ga Hyeon; Kim, Yu-Jeong; Lee, Yukyung; Jung, Suk-Chae; Seo, Hwi Won; Kim, Jun-Seob (Frontiers in Nutrition, 2023)
Green banana flour can be used as a prebiotic due to its ability to promote gut health and provide several health benefits. In this study, we investigated whether feeding mice green banana flour at different doses would alter intestinal microbiota composition. We fed C57BL/6N mice either a Low-dose (500 mg/kg/day) or High-dose (2000 mg/kg/day) of green banana flour daily for 3 weeks, and fecal samples were collected on days 0, 14, and 21 for microbiota analysis. Our results showed that the composition of intestinal microbiota was significantly altered by day 21, regardless of the dose. Notably, the consumption of green banana flour increased the presence of beneficial bacteria, including Coriobacteriaceae_UCG-002, Turicibacter, Parasutterella, Gastranaerophilales_ge, and RF39_ge. These changes in the intestinal microorganisms were accompanied by increased biological processes such as amino acid biosynthesis and secondary metabolite biosynthesis. Conversely, the consumption of green banana flour resulted in a decrease in biological processes related to carbohydrate degradation, glycerol degradation, and similar functions. These results emphasize the potential of green banana flour as a prebiotic that can benefit the gut microbiome.